Limited benefits of organic management and fungicide reduction to ground beetles in vineyards - Julia T. Gieser; Sebastian Kolb; Jo Marie Reiff; Kai Riess; Maura Hunke; Martin H. Entling; Jens Schirmel (Conservation Science and Practice)
Abstract The use of fungicides in agriculture can reduce animal biodiversity. Such non‐target effects could be mitigated through fungus‐resistant cultivars that reduce the need for fungicide applications. Hence, we conducted a study in 32 commercial vineyards in southwest Germany. We investigated the effect of fungicide spraying intensities (susceptible vs resistant cultivars) and management (conventional vs organic) on ground beetles as a widely used indicator group in agroecological studies. In addition, we examined the effects of local habitat conditions (e.g., microclimate, vegetation) and landscape characteristics. Fungicide applications were reduced by half in conventional, and almost by two‐thirds in organic vineyards with fungus‐resistant cultivars, compared to susceptible grape varieties in the same management regime. While there was no evidence that fungus‐resistant cultivars positively affect the diversity of ground beetles, organic management doubled the number of individuals of conservation‐relevant species per vineyard. Additionally, the proportion of semi‐natural habitats in the surrounding landscape, and the vegetation height significantly affected the species composition across vineyards. We conclude that local habitat conditions and landscape characteristics influence ground beetles more than the fungicide spraying intensity. Additional measures such as organic management, moderate ground vegetation management, and landscape diversification are needed for the conservation of ground beetles in viticulture.